A Nanoscaffold Impregnated With Human Wharton's Jelly Stem Cells or Its Secretions Improves Healing of Wounds. Issue 4 (April 2014) - Tam, Kimberley; Cheyyatraviendran, Suganya; Venugopal, Jayarama; Biswas, Arijit; Choolani, Mahesh; Ramakrishna, Seeram; Bongso, Ariff; Fong, Chui‐Yee
ABSTRACT Wound healing is a major problem in diabetic patients and current methods of treatment have met with limited success. Since skin cell renewal is under the control of mesenchymal stem cells (MSCs) treatment of wounds has been attempted with the application of exogenous bone marrow MSCs (hBMMSCs). However, hBMMSCs have the limitations of painful harvest, low cell numbers and short‐lived stemness properties unlike MSCs from the Wharton's jelly of human umbilical cords (hWJSCs). Since nanoscaffolds provide three dimensional architectural patterns that mimic in vivo stem cell niches and aloe vera has antibacterial properties we evaluated the use of an aloe vera‐polycaprolactone (AV/PCL) nanoscaffold impregnated with green fluorescent protein (GFP)‐labeled hWJSCs (GFP‐hWJSCs + AV/PCL) or its conditioned medium (hWJSC‐CM + AV/PCL) for healing of excisional and diabetic wounds. In skin fibroblast scratch‐wound assays exposed to GFP‐hWJSCs + AV/PCL or hWJSC‐CM + AV/PCL, fibroblasts migrated significantly faster from edges of scratches into vacant areas together with increased secretion of collagen I and III, elastin, fibronectin, superoxide dismutase, and metalloproteinase‐1 (MMP‐1) compared to controls. After one application of GFP‐hWJSCs + AV/PCL or hWJSC‐CM + AV/PCL excisional and diabetic wounds in mice showed rapid wound closure, reepithelialization, and increased numbers of sebaceous glands and hair follicles compared to controls. The same wounds exposed to GFP‐hWJSCs + AV/PCL or hWJSC‐CM + AV/PCL also showed positive keratinocyte markers (cytokeratin, involucrin, filaggrin) and increased expression of ICAM‐1, TIMP‐1, and VEGF‐A compared to controls. AV/PCL nanoscaffolds in combination with hWJSCs appear to have synergistic benefits for wound healing. J. Cell. Biochem. 115: 794–803, 2014. © 2013 Wiley Periodicals, Inc.